Divine Echoes: the Spiritual Significance of Thunder and Lightning across Religions - Belay Sitotaw Goshu; Muhammad Ridwan (Britain International for Academic Research (BIAR) Publisher, 2024)
This study traces the progression of human knowledge from ancient mythical interpretations to contemporary scientific explanations, investigating the cultural significance of thunder and its role in the development of scientific thought. The goal is to explore how thunder has impacted scientific perspectives and cultural ideas throughout history the shift from supernatural explanations to empirical data and the application of artificial intelligence to modern weather forecasting. The process comprises a review of historical and contemporary scientific literature thus, a textual examination of religious texts from many traditions, such as the Bible, Quran, and Vedas. The findings suggest that although thunder was originally thought to be a sign from God, scientific progress, especially during the Enlightenment, has led to a better understanding of thunder as a meteorological event. Furthermore, the modern world is still impacted by the ancient cultural respect for thunder in popular culture, literature, and the arts. The study concludes that the transformation of thunder's meaning from a representation of divine anger to an occurrence with scientific explanations reflects the advancement of human cognition and the fusion of scientific knowledge with cultural legacies. This knowledge emphasizes how crucial it is to see natural occurrences via cultural and scientific glasses, appreciating the influence of customs while embracing technological progress.